The kidnapped king - Roy, Ron, 1940-; Gurney, John (New York : Random House, 2000)
Dink and his friends meet an exchange student, Sammi, who is actually the prince of an island country, hiding from those enemies who have kidnapped his parents and who may be after him as well
"A stepping stone book."
"Grades 2-4"--P. [4] of cover
Keywords: Kidnapping -- Fiction; Princes -- Fiction; Mystery and detective stories